An Analysis of the use of metaphor in song lyrics on ANRI's album Timely! - Wisnu Dwi Mulyanto; Yoyok Nugroho (Japanese Research on Linguistics, Literature, and Culture, 2026)
This study aims to analyze the use of conceptual metaphors in the lyrics of ANRI's album "Timely!!" This study uses a descriptive qualitative approach with a cognitive linguistics framework. The research object is the song lyrics from the album "Timely!!," which consists of 11 songs. Data filtering was performed using Krippendorff's content analysis to identify the songs with the highest metaphor density. This resulted in five songs as the focus of analysis: "Cat's Eye," "Windy Summer," "Stay By Me," "A Hope from Sad Street," and "Remember Summer Days". The results show that the conceptual metaphors identified include structural, orientational, and ontological, with ontological metaphors dominating. Metaphors are used to conceptualize emotions, interpersonal relationships, and life experiences by mapping from concrete to abstract domains. These findings suggest that the lyrics of the album "Timely!!"  systematically utilize conceptual metaphors to construct poetic and communicative emotional meanings.